Correlation between Homeostatic Model Assessment-estimated Insulin Resistance (HOMA-IR) with Asymmetric Dimethylarginine (ADMA) in Prehypertension - Maria Evi Novianti; Syakib Bakri; Mansyur Arif; Ferry Sandra (The Indonesian Biomedical Journal, 2013)
BACKGROUND: Not only hypertension, prehypertension has been reported to be linked with increased cardiovascular morbidity and mortality risks as well. Prehypertension has three-fold hypertension and two-fold cardiovascular risks. Pathomechanism that links hypertension with cardiovascular is related with endothelial dysfunction and insulin resistance. Endothelial dysfunction occurs when nitric oxide (NO) biological function was impaired, whereas shown by asymmetric dimethylarginine (ADMA). Subjects with prehypertension had higher insulin resistance events than normotension, whereas shown by homeostatic model assessment-estimated insulin resistance (HOMA-IR). This research was conducted to investigate the correlation of HOMA-IR with ADMA in prehyper- and normo-tension.METHODS: A cross-sectional comparative research was designed. Subjects were recruited and divided into prehyper- and normo-tensive groups. ADMA was measured using ELISA method, while HOMA-IR was calculated by the ratio of fasting insulin and glucose. Spearman 1-tail and Mann Whitney statistical analyses were performed.RESULTS: Comparing to normotensive group, elevated levels of HOMA-IR and ADMA in prehypertensive group were shown, but not significant. In prehypertensive group, we found significant correlation between HOMA-IR and ADMA.CONCLUSION: Insulin resistance and endothelial dysfunction was elevated in prehyper-compared to normotension.KEYWORDS: prehypertension, insulin resistance, endothelial dysfunction, HOMA-IR, ADMA